The Influence of Ethical Leadership on Employee Engagement: Analyzing the Role of Work-Life Balance as a Mediating Variable - Silalahi, Marto; Hadikusumo, Reina A.; Simatupang, Sudung; Putra, Hendrick Sasimtan; Sudirman, Acai (International Journal of Business, Law, and Education, 2024)
In the context of the creative economy industry, which is often characterized by a dynamic work environment and high work expectations, employee engagement is crucial to increase productivity and retain the best talent. This study aims to analyze the effect of ethical leadership on employee engagement by considering work-life balance as a mediating variable in the creative economy industry in Indonesia. The sample used was 150 respondents, determined by the purposive sampling method, and then analyzed using the SEM-PLS method. The results of this study confirm that ethical leadership has a positive and significant effect on work-life balance. Furthermore, ethical leadership and work-life balance positively and significantly affect employee engagement. The mediation effect analysis also proves that work-life balance can mediate the relationship between ethical leadership and employee engagement. This study is expected to provide new insights into how ethical leadership can effectively increase employee engagement through work-life balance and provide practical recommendations for leaders to support employee well-being in this competitive industry.